Blau syndrome with hypertension and hepatic granulomas: a case report and literature review - Yao, Fangling; Tan, Bei; Wu, Di; Shen, Min (Frontiers in Pediatrics, 2023)
Background Blau syndrome (BS) is a monogenic disorder caused by NOD2 gene variants characterized by the triad of granulomatous polyarthritis, rash, and uveitis. Atypical symptoms were recognized in one-third to one-half of individuals with BS. This study aims to describe the clinical features of BS patients with hypertension and digestive system involvement. Methods The complete clinical data of a BS patient complicated with hypertension and hepatic granulomas were collected and documented. We also performed a literature search to find all reported cases of BS with hypertension and digestive system involvement. Results We reported the case of a 19-year-old man who presented with early onset symmetric polyarthritis and hypertension at age 5 and hepatic granulomas and cirrhosis at age 19. He was diagnosed with BS by the finding of a variant of the NOD2 gene (R334W). Through the literature review, 24 patients with BS were found who were reported to have hypertension, and 38 patients were found who had different digestive system manifestations such as hepatic granulomas, hepatosplenomegaly, diverticulitis, and intestinal granuloma. Among the 38 BS patients with digestive system involvement, 14 had hepatic granulomas proven by liver biopsy. Conclusions Hypertension and digestive system involvement are rare manifestations of BS. Clinicians, especially rheumatologists, must be aware of atypical symptoms of BS.